A extrafiscalidade do imposto de renda como incentivo fiscal à sustentabilidade ambiental - Silva, Luiz Otávio da (2016)
The objective of this research was to analyze and discuss the income tax on your extrafiscal aspect as encouraging environmental sustainability, having in mind that the Brazilian legal system admits extrafiscal taxation available to the State to intervene in the economic and social , with the purpose of encouraging sustainable development. Considering the fact that today is not conceived disassociated economic development of the environmental protection and conservation idea, the principles were studied, the rules and administrative instruments of the Tax Environmental Law aimed at ensuring the preservation of the environment and repair the damage to it caused. The Federal Constitution, in Article 225, caput, raised the fundamental right to level the ecologically balanced environment, essential to a healthy quality of life. The fundamental nature of the right to the environment is self-administered, inalienable, inalienable and imprescriptible, imposing both the Government and society, duty, and not merely an option, to defend it and preserve it for present and future generations. This study demonstrated that to the extent that the Constitution and other provisions that make the law establish such duties to the state, also provide you with the legal and financial means that need to meet the expenses that the fulfillment of these tasks lead you. In this sense, the same as that assigned to it certain responsibilities and duties is also granted him the power to tax, which incorporates two important elements: the collection of financial resources and intervention in the economic domain, aiming to stimulate or discourage certain behaviors. In the second element sets up the tax extrafiscality that can provide a variety of purposes, including the protection and defense of the environment, when, therefore, the tax is not just tax collection purpose, but seeks to curb the economic agents make environmentally undesirable choices or even encourage other desirable under environmental perspective. Thus, the tax extrafiscality assumes the state instrument task of preserving the environment, when the tax is used by the state to encourage environmentally friendly behavior. The methodology used in this research was the deductive method; as the means we used the bibliographic research, consultation with the books, web sites, jurisprudence and doctrine and, for purposes of the research was qualitative.